Computer performance evaluation and benchmarkin SPEC Benchmark Workshop 2009, Austin, TX, USA, January 25, 2009 : proceedings - SPEC Benchmark Workshop (Lecture notes in computer science, 2009)
This book constitutes the proceedings of the SPEC Benchmark Workshop 2009 held in Austin, Texas, USA on January 25th, 2009. The 9 papers presented were carefully selected and reviewed for inclusion in the book. The result is a collection of high-quality papers discussing current issues in the area of benchmarking research and technology. The topics covered are: benchmark suites, CPU benchmarking, power/thermal benchmarking, and modeling and sampling techniques. Benchmark Suites -- SPECrate2006: alternatives considered, lessons learned -- SPECjvm2008 performance characterization -- CPU benchmarking -- Performance Characterization of Itanium® 2-based Montecito processor -- A tale of two processors: revisiting the RISC-CISC Debate -- Investigating cache parameters of x86 family processors -- Power/thermal benchmarking -- The next frontier for power/performance benchmarking: energy efficiency of storage subsystems -- Thermal design space exploration of 3D die stacked multi-core processors using geospatial-Based predictive models -- Modeling and sampling techniques -- Generation, validation and analysis of SPEC CPU2006 simulation points based on branch, memory and TLB characteristics --A note on the effects of service time distribution in the M/G/1 queue.